Sanki-bir-boyutlu Kavitasyonlu Lüle Akışlarının Yeni Kabarcık Gaz Basıncı Yasasıyla Modellenmesi - Delale, Can Fuat; Morkoyun, Uğurcan; Kaya, Mehmet; Pasinlioğlu, Şenay; Ayder, Erkan (Niğde Ömer Halisdemir Üniversitesi, 2019)
The aim of this study is to develop a hydrodynamic cavitation model that is compatible with the results of the experiments and that can be adapted to commercial software. For this reason a hydrodynamic cavitation model that takes into account all of the damping mechanisms using the novel bubble gas pressure law is developed for quasi-one-dimensional bubbly cavitating nozzle flows. In this model the bubbly liquid is assumed to be a twophase homogeneous mixture, the Rayleigh-Plesset equation is employed for bubble dynamics, and bubble nucleation process is neglected. The first order system of equations thus obtained for quasi-one-dimensional cavitating nozzle flows is transformed into an initial value problem for the bubble radius and the pressure coefficient. A numerical code is then written to solve this initial value problem by the adaptive step size RungeKutta-Fehlberg method. Results obtained at the experimental conditions were compared and interpreted with the results of experiments.

Bu çalışmanın amacı, deney sonuçlarıyla uyumlu ve ticari yazılımlara uyarlanabilen bir hidrodinamik kavitasyon modelinin geliştirilmesidir. Bunun için sanki-bir-boyutlu kabarcıklı kavitasyonlu lüle akışları için yeni kabarcık gaz basıncı yasası kullanılarak kabarcık sönüm mekanizmalarını içerecek şekilde bir hidrodinamik kavitasyon modeli geliştirilmiştir. Bu modelde kabarcıklı sıvı iki-fazlı homojen karışım olarak ele alınmış, kabarcık dinamiği için Rayleigh-Plesset denklemi kullanılmış ve kabarcık çekirdekleşmesi göz önünde bulundurulmamıştır. Böylece sanki-bir-boyutlu kavitasyonlu lüle akışları için elde edilen denklem sistemi, kabarcık yarıçapı ve basınç katsayısı için birinci mertebeden denklem sistemi için başlangıç değer problemine dönüştürülmüştür. Başlangıç değer probleminin sayısal çözümü için Runge-Kutta-Fehlberg uyarlanmış adım büyüklüğü yöntemi kullanılmış ve elde edilen sonuçlar deney sonuçlarıyla karşılaştırılarak yorumlanmıştır.
Keywords: Kavitasyonlu lüle akışlar; Kabarcık dinamiği; Kavitasyon modelleri; Fizik, Uygulamalı